Alcohol use variability in a community-based sample of nonstudent emerging adult heavy drinkers. (1st November 2016) - Lau-Barraco, Cathy; Braitman, Abby L.; Stamates, Amy L.; Linden-Carmichael, Ashley N.
ABSTRACT: Background : While nonstudent emerging adults are at elevated risk for experiencing alcohol-related problems, there remains a paucity of research devoted specifically to addressing drinking in this group. Objectives : The present study sought to offer unique insights into nonstudent drinking by examining drinking variability across 30 days using a retrospective diary method. Specific aims were to: (1) compare within- and between-person variability in alcohol use across 30 days, and (2) determine the extent to which central social-cognitive between-person factors (i.e., social expectancies, perceived drinking norms, social drinking motivations) predict between-person alcohol use as well as within-person variability in drinking. Methods : Participants were 195 (65.1% men) nonstudent emerging adults recruited from the community with a mean age of 21.9 ( SD = 2.1) years. Results : Findings showed that a substantial portion of variation in daily alcohol consumption was attributable to the within-person (83%) rather than between-person (17.2%) level. Social expectancies, perceived drinking norms, and social motives were found to influence variability in daily alcohol consumption. Conclusion : Our findings contribute to knowledge that could guide efforts to design and tailor intervention strategies to minimize the harms experienced by an understudied and at-risk population of drinkers.